THE LEVEL OF INTEREST AND INFORMATION LITERACY OF STUDENTS OF THE MAKASSAR TOURISM POLYTECHNIC IN LEARNING ISLAM - Abidin, Saenal (Jurnal Diskursus Islam, 2021)
This study focused on the level of interest and information literacy of students in learning Islam, particularly at the Makassar Tourism Polytechnic campus. According to the researcher, it is necessary to research this issue to find out the extent of the information literacy skills and interest of the students of Tourism Polytechnic in improving their knowledge of Islam and the extent of their readiness to apply the knowledge they obtain in society. This study used a descriptive method with a quantitative approach. Data were collected using a questionnaire by employing a Likert scale. The results showed that the average students’ interest in learning Islam was 65.25% or categorized in the high level However, this figure had not yet reached a very high level. Therefore, motivation and more effective and fun teaching methods for students are needed to improve their interests. Meanwhile, the average level of media literacy skills was 79.38 or categorized in the high level. On average, they had been able to use information media as a learning resource independently. They had implemented part of the information literacy model, which was the identification of needs before searching. Regarding the literature they chose to access to information, they tended to prefer instant access to information, which was the internet. Meanwhile, interest in printed books was very low. Therefore, they require a good understanding and education on how to trace valid information through various relevant information media.